PENGARUH KUALITAS ASET, LIKUIDITAS, RENTABILITAS DAN EFISIENSI OPERASIONAL TERHADAP RASIO KECUKUPAN MODAL - Winda Parascintya Bukian, Ni Made; Merta Sudiartha, Gede (E-Jurnal Manajemen; Vol 5 No 2 (2016), 2016)
The aims of this study to determine the effect of asset quality (NPL), liquidity (LDR), profitability (ROA) and operational efficiency (BOPO) on capital adequacy ratio (CAR) banking at Indonesian Stock Exchange year 2013-2014. Sample of this study taken at Indonesian Stock Exchange accessed on website www.idx.co.id and obtained banking annual report data. Population that used in this study is all banking company registered on Indonesian Stock Exchange as much 42 banking company and sample determined by purposive sampling method so received samples as much 32 banking company completed the criteria. Data analysis technique used is multiple linear regression analysis by using SPSS (Statistical Program and Service Solution) 17.0 program. The result of this study prove NPL and LDR give positive effect and significant to CAR, ROA and BOPO give negative effect and significant to CAR.
Keywords: Asset Quality; Liquidity; Capital Adequacy Ratio